2023
DOI: 10.3389/feart.2023.1143380
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale convective systems in the third pole region: Characteristics, mechanisms and impact on precipitation

Abstract: The climate system of the Third Pole region, including the (TP) and its surroundings, is highly sensitive to global warming. Mesoscale convective systems (MCSs) are understood to be a vital component of this climate system. Driven by the monsoon circulation, surface heating, and large-scale and local moisture supply, they frequently occur during summer and mostly over the central and eastern TP as well as in the downstream regions. Further, MCSs have been highlighted as important contributors to total precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 162 publications
0
7
0
Order By: Relevance
“…The GPM IMERG V06B precipitation product is an integrated retrieval data set from a network of GPM constellation satellite partners (Huffman et al., 2019), with a temporal resolution of 30 min and a spatial resolution of ∼10 km. Previous evaluation studies over the U.S. and China suggested that the MCS tracking results by using GPM IMERG precipitation product provides consistent results with those derived from ground‐based radar data (Feng et al., 2021; Kukulies et al., 2021, 2023; Wu et al., 2023). It should be noted the hourly precipitation intensity could be changed due to the changes in the satellite constellation contributing to GPM IMERG, therefore, the efforts have been taken to ensure a seamless transition from TRMM to GPM (Huffman et al., 2019; Tan et al., 2019), and Tang et al.…”
Section: Methodsmentioning
confidence: 62%
“…The GPM IMERG V06B precipitation product is an integrated retrieval data set from a network of GPM constellation satellite partners (Huffman et al., 2019), with a temporal resolution of 30 min and a spatial resolution of ∼10 km. Previous evaluation studies over the U.S. and China suggested that the MCS tracking results by using GPM IMERG precipitation product provides consistent results with those derived from ground‐based radar data (Feng et al., 2021; Kukulies et al., 2021, 2023; Wu et al., 2023). It should be noted the hourly precipitation intensity could be changed due to the changes in the satellite constellation contributing to GPM IMERG, therefore, the efforts have been taken to ensure a seamless transition from TRMM to GPM (Huffman et al., 2019; Tan et al., 2019), and Tang et al.…”
Section: Methodsmentioning
confidence: 62%
“…The GPM IMERG V06B precipitation product is an integrated retrieval data set from a network of GPM constellation satellite partners (Huffman et al, 2019), with a temporal resolution of 30 min and a spatial resolution of ∼10 km. Previous evaluation studies over the U.S. and China suggested that the MCS tracking results by using GPM IMERG precipitation product provides consistent results with those derived from ground-based radar data (Feng et al, 2021;Kukulies et al, 2021Kukulies et al, , 2023Wu et al, 2023). It should be noted the hourly precipitation intensity could be changed due to the changes in the satellite constellation contributing to GPM IMERG, therefore, the efforts have been taken to ensure a seamless transition from TRMM to GPM (Huffman et al, 2019;Tan et al, 2019), andTang et al (2020) documented that there is little difference between the TRMM era (2013) and GPM era (2014)(2015), which indicates that GPM IMERG is quite robust in the transition between the two eras.…”
Section: Observational Reanalysis Datasets and Model Simulations Usedmentioning
confidence: 60%
“…Several definitions using various cloud system parameters and thresholds have been used in the literature to provide an objective classification of MCS, preventing actual quantitative comparisons (e.g., recent reviews by Kukulies et al. (2023)). Houze (2004) broadly defined MCSs as “…a cumulonimbus cloud system that produces a contiguous precipitation area ∼100 km or more in at least one direction.” We translate this definition into objective rules, which can be used in tracking algorithms, and can be applied to satellite‐based observations.…”
Section: Methodsmentioning
confidence: 99%